2012
DOI: 10.3741/jkwra.2012.45.9.887
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Drought Severity over South Korea using Standardized Precipitation Evapo-transpiration Index (SPEI)

Abstract: Drought is a non-negligible disaster of nature and it is mainly caused by rainfall shortage for a long time though there are many definitions of drought. 'Standard Precipitation Index' (SPI) that is widely used to express the level of meteorological drought intensity has a limit of not being able to consider the hydrological changes such as rainfall and evapotranspiration caused by climate change, because it does not consider the temperature-related variables other than the precipitation. Recently, however, 'S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 16 publications
2
11
0
2
Order By: Relevance
“…During the past 30 years, Korea suffered from the severe drought damage at least once every 5-8 years [30,42]. In addition, moderate drought has happened annually in the regional and national area since 1990 [42].…”
Section: Site Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past 30 years, Korea suffered from the severe drought damage at least once every 5-8 years [30,42]. In addition, moderate drought has happened annually in the regional and national area since 1990 [42].…”
Section: Site Descriptionmentioning
confidence: 99%
“…A few studies have evaluated the drought using SPEI based on the Thornthwaite equation for calculating evapotranspiration [30]. The evapotranspiration is related to several factors, including temperature, precipitation, wind, humidity, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Even though our findings from crop yields suggest the contrary due to the predominance of cereal croplands in northcentral regions of Spain, this can be attributed to episodes of abnormal extreme temperatures, such as the very low temperatures in early spring or warmer than usual temperatures in winter. These would affect the expected low evapotranspiration rates during the cold season (Fontana et al, 2015;Kolář et al, 2014). A recent study by Hernandez-Barrera et al (2016) demonstrated that during autumn and spring, precipitation deficit is the most influential climate factor affecting wheat growth, while an increase in the diurnal temperature range causes a reduction in wheat yield.…”
Section: Discussionmentioning
confidence: 99%
“…During the past 30 years, Korea suffered from the severe drought damage at least once every 5-8 years (KRC, 2001; Kim et al, 2012). In addition, the moderate drought has been happened annually in the regional and national area, since 1990.…”
Section: Analysis Of Seasonal and Regional Drought In South Korea Usimentioning
confidence: 99%
“…A few studies evaluated the drought using SPEI based on Thornthwaite equation for calculating evapotranspiration (Kim et al, 2012;Kim et al, 2013). The evapotranspiration is related to several factors such as temperature, precipitation, wind, and humidity etc.…”
Section: Introductionmentioning
confidence: 99%